2009
DOI: 10.1152/ajpheart.00738.2009
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of vascular smooth muscle and endothelial cell proliferation in vitro and in vivo by cAMP/PKA-activated p85αPI3K

Abstract: cAMP inhibits proliferation in most cell types, triggering different and sometimes opposing molecular pathways. p85alpha (phosphatidylinositol 3-kinase regulatory subunit) is phosphorylated by cAMP/PKA in certain cell lineages, but its effects on vascular smooth muscle cells (VSMCs) and endothelial cells (ECs) are unknown. In the present study, we evaluated 1) the role of p85alpha in the integration of cAMP/PKA-dependent signaling on the regulation of VSMC and EC growth in vitro; and 2) the effects of PKA-modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…cAMP induces proliferation in FRTL5 thyroid cell (42,43), while it inhibits proliferation in NIH 3T3 (44). A differential regulation of VSM and endothelial cell proliferation, by cAMP/PKA-activated p85α PI3K has also been described (39). In our model cAMP treatment is able to reduce cell proliferation in all conditions examined.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…cAMP induces proliferation in FRTL5 thyroid cell (42,43), while it inhibits proliferation in NIH 3T3 (44). A differential regulation of VSM and endothelial cell proliferation, by cAMP/PKA-activated p85α PI3K has also been described (39). In our model cAMP treatment is able to reduce cell proliferation in all conditions examined.…”
Section: Discussionsupporting
confidence: 55%
“…In fact the phosphorylation of p85α PI3K Ser83 inhibits cell proliferation in fibroblasts and VSMC, while it is essential for the correct cell cycle progression in thyroid cells, and does not affect cell proliferation of endothelial cells (9,10,39). Our results show that phosphorylation of p85α PI3K Ser83 is essential for MCF7 cell survival and proliferation, as demonstrated by the low growth rate observed in cells overexpressing the p85A mutant.…”
Section: Discussionmentioning
confidence: 50%
“…In this way, rat carotid arteries were locally transfected with FLAG 49 ) VSMC and Endothelial Regeneration After Stenting tagged plasmid vectors expressing p85 WT , p85 PKA-inactive , and p85 PKA-activated immediately after balloon injury. 48 In this elegant experiment, we demonstrated that local delivery of p85 PKA-activated prevents VSMC proliferation and NIH after experimental balloon injury, and that p85 PKA-activated local delivery does not affect endothelial regeneration in rat balloon-injured arteries.…”
Section: Effect Of Endothelial Regeneration and Vsmc Proliferation Onmentioning
confidence: 75%
“…Our experimental contribution to understanding the molecular and cellular determinants of smooth muscle and endothelium in restenosis and NIH comes from vascular gene transfer of dominant negative mutants of the regulatory subunit of the phosphatidylinositol 3-kinase, namely p85. 48 Indeed, we recently investigated the effects of overexpression of p85α PI3K plasmids in rat carotid arteries subjected to balloon injury, by using pluronic F127 gel as the sustained-release polymer. In this way, rat carotid arteries were locally transfected with FLAG 49 ) VSMC and Endothelial Regeneration After Stenting tagged plasmid vectors expressing p85 WT , p85 PKA-inactive , and p85 PKA-activated immediately after balloon injury.…”
Section: Effect Of Endothelial Regeneration and Vsmc Proliferation Onmentioning
confidence: 99%
“…Torella et al (6) further investigated signaling events triggered by pSer83-p85␣ overexpression in EC and VSMC cell culture and demonstrated that pSer83-p85␣ binds to Ras and inhibits ERK-1/2 activation in VSMCs but not in ECs. These results suggest a cAMP-and PKA-independent but ERK-1/2-dependent mechanism of EC proliferation, suggesting that EC and VSMC proliferation are regulated by multiple redundant pathways, among which ERK-1/2 activation is inessential for EC, but essential for VSMC, proliferation.…”
mentioning
confidence: 99%